Experience of laparoscopic ovarian drilling in the treatment of infertility associated with polycystic ovary syndrome in women - Yu.E. Dobrokhotova; I.I. Grishin; O.R. Oguede; I.Yu. Ilina (LCC «Medicine-Inform», 2023)
Yu.E. Dobrokhotova, I.I. Grishin, O.R. Ogede, I.Yu. Ilyina Pirogov Russian National Research Medical University, Moscow, Russian Federation The article presents the author's experience concerning laparoscopic ovarian drilling (LOD) in women with infertility associated with polycystic ovary syndrome (PCOS). The study included 23 female patients aged 18-35 years with infertility associated with PCOS, who were treated with clomiphene citrate for 6 months without effect. All patients underwent LOD with electrocoagulation. The follow-up period after surgery was 3 years. Pregnancy occurred in 10 (43.5%) of the female patients within a year after the LOD, and in 13 (56.5%) - pregnancy occurred within 2-3 years. There was a difference in the pregnancy frequency during the year between female patients under 30 y.o. (9 (39.2%)) and over 30 y.o. (11 (47.8%)). Pregnancy occurred less frequently in patients over 30, however, due to the small number of patients, the presented results were not statistically significant. Thus, it requires further follow-up and confirmation of this conclusion. It was also revealed that the shorter the infertility duration, the greater the pregnancy likelihood after surgical treatment: pregnancy occurred in 9 (39.2%) female patients with infertility period of <3 years versus 1 (4.3%) female patient with infertility period of >3 years (RR 5.8, 95% CI 1.2-36.2). In conclusion, LOD can be used in female patients with resistance to clomiphene citrate. The ovulation restoration, and pregnancy and childbirth onset make LDL a possible alternative method of treatment with a lower risk of complications (ovarian hyperstimulation syndrome, multiple pregnancy). Keywords: infertility, pregnancy, treatment, laparoscopic ovarian drilling, polycystic ovary syndrome, gonadotropin resistance. For citation: Dobrokhotova Yu.E., Grishin I.I., Ogede O.R., Ilyina I.Yu. Experience of laparoscopic ovarian drilling in the treatment of infertility associated with polycystic ovary syndrome in women. Russian Journal of Woman and Child Health. 2023;6(3):265-269 (in Russ.). DOI: 10.32364/2618-8430-2023-6-3-8.